The occurrence characteristics and removal mechanism of residual water in marine shales: A case study of Wufeng-Longmaxi shale in Changning-Weiyuan area, Sichuan basin. (1st October 2019) - Chen, Zhiyuan; Song, Yan; Li, Zhuo; Liu, Shaobo; Li, Yaohua; Liu, Guoheng; Yang, Wei; Wang, Qianyou; Yang, Youdong; Gao, Fenglin
Highlights: Residual water mainly occurs in the pores associated with clay minerals, especially for the chlorite and illite. The residual water content in micropore and mesopore is higher, and the removal rate of water in micropore and mesopore is faster than that in macropore. The residual water occurred in the state of volume filling and surface adsorption differently determined by the pore radius. The residual water mainly exists in the pores with a diameter of 2–10 nm within the mesoporous range. Abstract: The shale gas production layer of Wufeng-Longmaxi Formation is characterized by ultra-low water saturation, affecting the reservoir adsorption capacity, self-sealing ability, water phase sealing ability, and the shale gas production. Therefore, we studied the occurrence characteristics and the removal mechanism of residual water in Wufeng-Longmaxi shale of Changning-Weiyuan area using the direct method, i.e., nuclear magnetic resonance (NMR), field emission-scanning electron microscopy (FE-SEM), focused ion beam-scanning electron microscopy (FIB-SEM), µm-CT), and the indirect methods., i.e., N2 adsorption, CO2 adsorption, and mercury intrusion porosimetry (MIP). The results showed that residual water mainly exists in the clay-related inorganic pores. Micropore and mesopore are better for the residue water occurrence, relating to a higher removal rate in the heating process. Distribution of water in micropore, mesopore, and macropore are different: volume filling and surface adsorption are equally same in the micropore, the volume-filled water is gradually absorbed by the surface, and then removed in the mesopore, while the pore water will be absorbed by the surface when the pore volume exceeds a certain value in the macropore. In addition, the residue water is prone to migrate from organic pore to inorganic pore and has a plugging effect on pores in the mesopore especially in the range of 2–10 nm.